2019
DOI: 10.17323/j.jcfr.2073-0438.13.2.2019.25-35
|View full text |Cite
|
Sign up to set email alerts
|

Do Overconfident CEOs Pay More to Shareholders? Evidence from the US Market

Abstract: This paper aims to discover evidence on the possible impact of CEO overconfidence on payout policy, and the role ofcorporate boards in offsetting the possible negative effects of this overconfidence. Our investigation demonstrates theeffect of overconfidence on the choice of payout method, specifically regarding the repurchases-dividends mix. Wealso evaluate the ability of corporate governance mechanisms to reduce or even eliminate the negative effects of CEObehavior on payout decisions.This study is conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…ESG practices may be seen as a new arena for company operations, where new situations need the development of new vocabulary and management procedures. Confident managers are more likely to not just overinvest, but also to increase their assets, especially riskier ones (Anilov, 2019). The inventiveness of such managers may have a positive impact on ESG implementation, as such CEOs are more likely to try new ways, enabling the business to flourish in this area (Gao et al, 2020).…”
Section: Ceo Characteristics+ Esgmentioning
confidence: 99%
“…ESG practices may be seen as a new arena for company operations, where new situations need the development of new vocabulary and management procedures. Confident managers are more likely to not just overinvest, but also to increase their assets, especially riskier ones (Anilov, 2019). The inventiveness of such managers may have a positive impact on ESG implementation, as such CEOs are more likely to try new ways, enabling the business to flourish in this area (Gao et al, 2020).…”
Section: Ceo Characteristics+ Esgmentioning
confidence: 99%
“…Regarded the interactive relationship between excessive managerial overconfidence and dividend policies, Seputra (2018) study indicated that a CEO who enjoys excessive managerial overconfidence is less inclined to pay cash dividends, and on the contrary, the results of most studies were (Deshmukh et al, 2013;Anilov, 2019;Vinh, 2020) addresses the positive impact of excessive managerial confidence on dividend policies on the premise that broadcasting good news about the corporation's estimates of future profits through dividends creates good indicators of the corporation's performance and deepens the optimistic view of prospective and current shareholders about the corporation's good financial situation in the form Which prompts the CEO to use dividend policies in order to create shareholder value that helps achieve the CEO's personal interests in leading the corporation.…”
Section: The Role Of the Board Under Managerial Overconfidencementioning
confidence: 99%